Report of the speeches delivered at the public meeting held in the Music Hall, Albion street, Leeds on Tuesday, June 18, 1861, Mr. ALderman Middleton, in the chair, to receive a deputation from Liverpool on the subject of financial reform (Baines, 1861)
Repr. from the "Leeds mercury", June 20, 1861.